Externalizing problems mediate the relation between teacher and peer violence and lower school performance. (January 2023) - Masath, Faustine Bwire; Scharpf, Florian; Dumke, Lars; Hecker, Tobias
Abstract: Background: The association between children's exposure to family violence and poor academic outcomes is well-established. Less is known about how exposure to violence in the school context, i.e., by teachers and by peers, affects academic functioning. Moreover, the role of children's mental health problems in this link has hardly been examined. Objectives: We examined direct and indirect associations between children's experiences of violence by teachers and peers and children's mental health and school functioning while controlling for children's experiences of parental violence. Participants: Using a multistage random sampling approach, we obtained a representative sample of 914 students (50.5 % girls, Mage = 12.58 years) from 12 primary schools in Tanzania. Methods: In structured interviews, students' experiences of violence and mental health problems were assessed. Students' academic performance and absenteeism were documented using school records. Associations were examined using structural equation modeling. Results: Experiences of more teacher and peer violence were each significantly associated with higher externalizing problems (teachers: β = 0.27 [95 %-CI: 0.12, 0.47]; peers: β = 0.17, [95 %-CI: 0.07, 0.32]). Higher externalizing problems were significantly associated with poorer academic performance (β = −0.13, [95 %-CI: −0.23, −0.02]), implying significant indirect associations between students' experiences of teacher violence (β = −0.04, [95 %-CI: −0.08, −0.01]) and peer violence (β = −0.02, [95 %-CI: −0.05, −0.01]) and their academic performance via externalizing problems. Conclusion: Exposure to violence at school may impair children's academic performance indirectly by increasing attention and behaviour problems. Further investigations in longitudinal studies and implementation of interventions to reduce violence in schools are indicated.